Pengolahan Sampah Organik Menjadi Pupuk Kompos Dengan Sistem Lubang Biopori Di Kelurahan Betungan - Irawan, Dicky; Wahyudi, Wahyudi; Maryeta , Delta; Indarti , Okta; Ulandari, Shelli; Azhari, Diah; Nur’aini, Hesti; Fariadi, Herri (Jurnal Kewirausahaan & Inovasi, 2025)
The problem of household organic waste accumulation is one of the new challenges in environmental management. One environmentally friendly and efficient solution is to utilize the biopore hole system as a method of processing organic waste into compost. Biopore holes are a simple technology in the form of vertical holes in the ground that function to accelerate the decomposition process of organic waste with the help of the activity of microorganisms and soil fauna. The purpose of this training is to increase public knowledge on how to process organic waste properly, while producing useful waste products such as compost. This activity is carried out in the form of lectures and practices, so that residents gain knowledge and skills in processing organic waste properly.